Genomic data provide new insights on the demographic history and the extent of recent material transfers in Norway spruce. (30th April 2019) - Chen, Jun; Li, Lili; Milesi, Pascal; Jansson, Gunnar; Berlin, Mats; Karlsson, Bo; Aleksic, Jelena; Vendramin, Giovanni G.; Lascoux, Martin
Abstract: Primeval forests are today exceedingly rare in Europe, and transfer of forest reproductive material for afforestation and improvement has been very common, especially over the last two centuries. This can be a serious impediment when inferring past population movements in response to past climate changes such as the last glacial maximum (LGM), some 18, 000 years ago. In the present study, we genotyped 1, 672 individuals from three Picea species ( P. abies, P. obovata, and P. omorika ) at 400K SNPs using exome capture to infer the past demographic history of Norway spruce ( P. abies ) and estimate the amount of recent introduction used to establish the Norway spruce breeding program in southern Sweden. Most of these trees belong to P. abies and originate from the base populations of the Swedish breeding program. Others originate from populations across the natural ranges of the three species. Of the 1, 499 individuals stemming from the breeding program, a large proportion corresponds to recent introductions from mainland Europe. The split of P. omorika occurred 23 million years ago (mya), while the divergence between P. obovata and P. abies began 17.6 mya. Demographic inferences retrieved the same main clusters within P. abies than previous studies, that is, a vast northern domain ranging from Norway to central Russia, where the species is progressively replaced by Siberian spruce ( P. obovata ) and two smaller domains, an Alpine domain and a Carpathian one, but also revealed further subdivision and gene flow among clusters. The three main domains divergence was ancient (15 mya), and all three went through a bottleneck corresponding to the LGM. Approximately 17% of P. abies Nordic domain migrated from P. obovata ~103K years ago, when both species had much larger effective population sizes. Our analysis of genomewide polymorphism data thus revealed the complex demographic history of Picea genus in Western Europe and highlighted the importance of material transfer in Swedish breeding program.